Successful Repositioning Procedure for Benign Paroxysmal Positional Vertigo after Stapedotomy - Željko Zubčić; Andrijana Včeva; Tihana Mendeš; Josip Maleš; Hrvoje Mihalj; Hrvoje Vidić; Matej Rezo; Ivan Abičić; Tin Prpić; Anamarija Šestak (Acta Clinica Croatica, 2022)
This report aimed to investigate the relationship after successful left‐sided stapedotomy and postoperative benign paroxysmal positional vertigo (BPPV) due to vitamin D deficiency. A 56‐year‐old woman presented with a complaint of progressive hearing loss and tinnitus in the left ear without dizziness. A successful left‐sided stapedotomy was performed, confirming the diagnosis of otosclerosis and closing the air‐bone gap to less than 10 dB. Seven days after the stapedotomy, the patient reported dizziness, usually when turning to her left side in the bed. An electrophysiological assessment was performed to investigate vestibular function. Dix Hallpike maneuver showed a typical response, about 5 seconds after repositioning the head, and geotropic, torsional rotary nystagmus of about 30 seconds was registered. Vitamin D deficiency in serum was found. Complete symptom remission was achieved after 7-day-treatment with Epley’s maneuver. As a postoperative vertigo complication, BPPV often remains unrecognized after stapes surgery. Canalith repositioning maneuver is treatment for BPPV. Determining serum levels of total calcium and vitamin D may play a significant role in monitoring and reducing the recurrence of dizziness.